Semiconductor Wastewater Treatment With Natural Starches As Coagulants Using Response Surface Methodology - Mohd Omar, Fatehah (2007)
The semiconductor wastewater used in this study was obtained from a multinational semiconductor company located in Penang. The characteristics of the semiconductor influent for the pH, chemical oxygen demand (COD), suspended solids (SS) and total solids (TS) are in the range of 4-6, 700-1550 mg/L, 0.014-0.24 mg/L and 8-188 mg/L, respectively. The Energy Dispersive X-ray (EDX) results revealed that the major composition of the semiconductor wastewater is silica.